2014
DOI: 10.1155/2014/613960
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Contamination of Commonly Consumed Fresh Leafy Vegetables in Benha, Egypt

Abstract: This study evaluated the degree of parasitic contamination of vegetables which are commercialized and consumed fresh in Benha, Egypt. It included 530 vegetables: lettuce, watercress, parsley, green onion, and leek. Vegetables were collected randomly from markets within Benha. Samples were washed in saline, and the resulting washing solution was filtered and centrifuged to concentrate the parasitic stages. Sediments and supernatants were examined by iodine and modified Ziehl-Neelsen stained smears. Intestinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
107
11
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(157 citation statements)
references
References 22 publications
(49 reference statements)
23
107
11
16
Order By: Relevance
“…Our findings are consistent with previous studies that reported higher rates of parasitic contamination and diversity during the dry season than during the monsoon season (Monge et al 1996;Uga et al 2009). Studies performed in Alexandria and Benha, Egypt, showed higher rates of parasitic diversity and contamination of raw vegetables during the warm season than during the cold season (El Said Said 2012; Eraky et al 2014). The low diversity of parasites during the monsoon season could be explained by the parasitic eggs on the surface of the vegetables being washed away by the rain as assumed by Uga et al (2009).…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are consistent with previous studies that reported higher rates of parasitic contamination and diversity during the dry season than during the monsoon season (Monge et al 1996;Uga et al 2009). Studies performed in Alexandria and Benha, Egypt, showed higher rates of parasitic diversity and contamination of raw vegetables during the warm season than during the cold season (El Said Said 2012; Eraky et al 2014). The low diversity of parasites during the monsoon season could be explained by the parasitic eggs on the surface of the vegetables being washed away by the rain as assumed by Uga et al (2009).…”
Section: Discussionmentioning
confidence: 93%
“…While this may at least, help explain why in the present study, lettuce and spinach were contaminated the most (14.58% and 13.54%, respectively) and green pepper (3.13%), the least, other factors may as well be important. Lettuce was the vegetable contaminated most commonly in Maiduguri, northeast Nigeria (Adamu et al, 2012), Ankara, Turkey (Kozan et al, 2005), Riyadh, Saudi Arabia (Al-Megrin, 2010) and Benha, Egypt (Eraky, Rashed, Nasr, El-Hamshary, & El-Ghannam, 2014). In some studies however, other vegetables including spinach (Maikai et al, 2012) and rocket (Said, 2012) were contaminated the most.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great importance of a diet rich in this kind of food, the habit of consuming poorly washed raw vegetables could expose individuals to the risk of infection by several microorganisms, such as intestinal parasites and commensals, since protozoan cysts and helminth eggs and/or larvae can be conveyed along with them 3 . The number of human infections and outbreaks associated with the consumption of raw vegetables contaminated with these foodborne pathogens has increased in the past decades, mainly in developing countries, where they represent a public health concern that is still underestimated 4,5 .…”
Section: Introductionmentioning
confidence: 99%